(untitled) (Journal of Renal and Hepatic Disorders, 2018)
Cardiac dysrhythmia and sudden death account for a large proportion of cardiac mortality in dialysis patients. Risk factors for sudden death that are specific to dialysis patients include fluid and electrolyte imbalances during hemodialysis, particularly those of potassium. The risk of arrhythmia may be related to changes in serum K+ concentration during dialysis, and thus close attention should be paid to the dialysate K+ concentration and the serum–dialysate concentration gradient. Potassium profiling is a technique where the dialysate K+ concentration is gradually reduced to keep the gradient between blood and dialysate at a non-fluctuating low level. We provide a review of studies that compare constant potassium concentration in dialysate to gradual reduction in dialysate potassium concentration. These studies illustrate that adequate and more gradual potassium removal can be achieved with potassium profiling techniques, while having lower cardiac irritability.